Heritance Rights of Non-Muslim Heirs in Islamic Law: An Analysis of Case Study Decision No. 1578 / Pdt.G / 2010 / PA. JT - Rosida Rosida; Muhamad Taufik La Ode (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2023)
This article examines the barriers to inheritance in the context of the science of roses, with a specific focus on the impact of religious differences between heirs. Utilizing a normative juridical approach and employing library research, the study analyzes Islamic law's position on non-Muslim heirs' right to inherit property from Muslim heirs. The research findings reveal that Islamic law emphasizes the principle that non-Muslim heirs are generally excluded from inheriting assets as outlined in the Qur'an, Hadith, and Compilation of Islamic Law. Furthermore, the article explores a case study decision by the East Jakarta Religious Court (case number 1578/PDT.G/2010/PA. JT) that upheld the exclusion of non-Muslim heirs based on formal legal provisions, including the principle of Islamic personality and the nebis in idem case. The judge's decision has raised normative concerns as it appears to contradict the rules stated in the religious texts. The implications of this study shed light on the intersection of religious differences and inheritance rights within the Islamic legal framework.